Cryptococcal infection of the femur misdiagnosed as a primary bone tumor: A case report and literature review - Bin Liu; Yiyun Ni; Haifeng Zeng; Min Tang; Junnan Jiang (Journal of International Medical Research)
Cryptococcal infections are uncommon, and musculoskeletal involvement of the femur is extremely rare, often resulting in diagnostic challenges. A woman in her early 70s presented with a 20-day history of progressive left thigh pain that was aggravated by limb movement. Initial evaluation at a local hospital suspected a primary bone tumor based on radiographic findings of an osteolytic lesion in the midshaft of the left femur. Laboratory tests revealed elevated C-reactive protein level, erythrocyte sedimentation rate, and ferritin levels, but no malignant tumor markers were detected. Radiological assessment, including magnetic resonance imaging and whole-body scintigraphy, raised the suspicion of a primary bone tumor, with differential diagnoses including eosinophilic granuloma or Brodie’s abscess. An ultrasound-guided biopsy revealed spindle cell proliferation with multinucleated giant cells, with no evidence of malignancy. A multidisciplinary consultation attributed the finding to either an infectious etiology or a possible false-negative result of B-mode ultrasound-guided biopsy. The patient subsequently underwent debridement and biopsy of the affected bone in the left thigh. Although microbial cultures were negative, immunohistochemical analysis showed features consistent with cryptococcal infection. Special staining demonstrated the characteristic thick capsules of Cryptococcus spp., confirming the diagnosis of a cryptococcal granuloma in the left femur. Early diagnosis and timely treatment are important to effectively manage cryptococcal bone infections.